Analysis of copper and zinc content in the drinking water of Maracaibo city. A technical note - Ysambertt, F.; Paredes, J.; Márquez, N. (Rev. Téc. Fac. Ing. Univ. Zulia)
The content of Cu and Zn in the drinking water of Maracaibo city was evaluated using the High Performance Liquid Chromatography technique, Ultra Violet-Visible detection and Dithizone as chelating agent. This study showed that concentrations of Cu and Zn In the drinking water do not exceed the allowable limits. However, the average of Zn concentration was eight-fold higher with respect to the treated water at the plant effluent. Additionally the content of these metals was higher In the northern area of the city.